2013
DOI: 10.1016/j.jadohealth.2012.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Homelessness Experiences, Sexual Orientation, and Sexual Risk Taking Among High School Students in Los Angeles

Abstract: Purpose Prior studies reported homeless adolescents engage in more sexual risk than their housed peers. However, these comparisons are typically made post hoc by comparing homeless adolescent community-based samples with high school probability samples. This study utilizes a random sample of high school students to examine homelessness experiences and sexual risk behaviors. Methods A supplemental survey to the Youth Risk Behavior Survey containing questions regarding homelessness and sexual health was admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(29 citation statements)
references
References 16 publications
1
27
0
1
Order By: Relevance
“…However, LGBQ students were significantly more likely than heterosexual students to report having stayed in a public place and significantly less likely to report having stayed in a shelter. These results reinforce prior research that indicated LGBQ youth are less likely than their heterosexual peers to spend the night in a shelter, perhaps because they perceive greater stigma and discrimination at these sites . This is particularly problematic, because shelters are protective for youth experiencing homelessness and sleeping in a public place has several health consequences and increases the risk of victimization .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…However, LGBQ students were significantly more likely than heterosexual students to report having stayed in a public place and significantly less likely to report having stayed in a shelter. These results reinforce prior research that indicated LGBQ youth are less likely than their heterosexual peers to spend the night in a shelter, perhaps because they perceive greater stigma and discrimination at these sites . This is particularly problematic, because shelters are protective for youth experiencing homelessness and sleeping in a public place has several health consequences and increases the risk of victimization .…”
Section: Discussionsupporting
confidence: 84%
“…During the 2008‐2009 school year, public schools enrolled nearly 1 million homeless children and youth . Recent studies among high school students have found that sexual minority (ie, lesbian, gay, bisexual, and questioning—LGBQ) youth experience higher rates of homelessness than their heterosexual peers . This is especially problematic because LGBQ students are often at greater risk of negative outcomes like depression, suicidality, drug use, and academic difficulties …”
mentioning
confidence: 99%
“…Another contributing factor may be individual-level discrimination and bullying, which is still routinely experienced by SM youth and young adults (Gayles and Garofalo, 2012; Gower et al, 2017; Hatzenbuehler et al, 2015). Lack of family support may also be a salient risk factor, as SM youth report lower levels of parental closeness and higher rates of abuse and homelessness compared to heterosexual youth (Friedman et al, 2011; Pearson and Wilkinson, 2013; Rice et al, 2013). One review found that half of SM youth who come out to their parents experience rejection (Rosario and Schrimshaw, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…41,50,51 LGBTQ youth who are homeless report higher rates of survival sex, substance use, and victimization when compared with non-LGBTQ homeless youth. 41,[51][52][53] A survey by Cochran et al 51 comparing LGBT homeless youth and heterosexual homeless youth revealed that LGBT youth reported, on average, 7.4 more acts of sexual victimization than their heterosexual counterparts and had significantly higher rates of psychopathology. 50 LGBTQ youth also experience higher rates of depression and suicidality.…”
Section: Victims Of Abuse and Neglectmentioning
confidence: 99%